Meningkatkan Kemampuan Mengenal Huruf Melalui Media Pembelajaran Kolase Pada Anak Usia Dini - Novita Andriani Panjaitan; Erni Asneli Asbi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The key to learning to read well and effectively lies in the ability to recognize letters. Recognizing letters is a fundamental stage of learning to read and communicate that is important to apply to early childhood. Many children at an early age are less motivated in learning to recognize letters. This is because most teachers still use the teacher center method, so that children quickly feel bored in learning. Besides, the lack of learning media makes children less understand the subject matter presented by the teacher. The most important letter introduction tips of all is to make the process of learning to recognize letters more fun and not boring, one of which is by using collage learning media. The purpose of this practicum is to improve the ability to recognize letters through collage learning media for early childhood at the Namira Orphanage. The intervention used in this practicum is a micro intervention using the casework method through general stages consisting of; Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and ends with Termination.